Three Bleached Black Female Images and the Educational Significance in the Cane River - Tan, Qi (Journal of Theory and Practice of Contemporary Education, 2023)
The Cane River is the masterpiece of contemporary African American female writer Larita Tadmi. This is a documentary novel composed of three parts: "Susette", "Philomin", and "Emily". It tells the story of the growth process of three gradually "bleached" black women in the Tadmi family under the slave system in the 1830s, reflecting their slave life, family life, emotional status, and the fears they had to face. This article intends to analyze the image of black women who sacrifice for their children under the dual oppression of race and gender from the perspective of black feminist criticism. The aim is to expose the inhumane nature of slavery from a new perspective and showcase the optimistic, upward, independent, and strong spirit of black women.